MINI RESEARCH OF UMKM SURABAYA CHICKEN GREAT RESTAURANT (BUSINESS CAPITAL) - Andini; Frengki Putra Ramansyah; Muazzinah Tunnur; Multazam; Rahmat Idhami (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
Capital is an important component in the establishment and development of Micro, Small, and Medium Enterprises (MSMEs), especially in the culinary sector. This study analyzes the use of personal capital at Rumah Makan Ayam Geprek Surabaya as a form of MSME, with a focus on effectiveness in operational aspects and business development. Capital is divided into two types: initial capital (for equipment, renovation, and promotion) and operational capital (for raw materials, salaries, and utilities). Using a qualitative descriptive method, this study examines the competitive strategies and financial independence offered by the use of personal capital. The results show that self-funded MSMEs have higher flexibility, faster decision making, and lighter financial burdens, thus supporting sustainable business growth.